BELA NEGARA PERSPEKTIF KETAHANAN EKONOMI BERBASIS AL-QUR’AN - Faldiansyah, Iqrom; Anantha, Bimma (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
Globalization has a great influence on the fading of patriotism. The fading of patriotism causes the survival of a nation and state to be vulnerable due to the absence of efforts to defend the state. Whereas defending the country is the main pillar to maintain national security. In national security, one of the main pillars is economic resilience. Awareness of defending the state that has not been optimal and entrenched in people's lives makes economic resilience vulnerable. Moreover, the presence of the Covid-19 pandemic has triggered a trend of steep increases in unemployment and poverty rates in Indonesia. Therefore, the application of state defense to maintain economic resilience is an important at this time. This paper uses the literature study method. The novelty of the ideas offered in this paper is to maintain unity for the economic resilience and to apply unity in increasing economic resilience. The concept of this idea is here to provide an overview of state defense that can be carried out by all Indonesian citizens in order to maintain and improve economic resilience. This idea was born from the importance of maintaining unity as stated in the QS. Ali-Imran (03):103. With the presence of this paper, it is hoped that it can be a reflection of the application of state defense in maintaining and increasing economic resilience in Indonesia.